2010
DOI: 10.3844/ajessp.2010.238.243
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Rainfall Intensity using Hourly Data

Abstract: Problem statement: Design of storm water best management practices to control runoff and water pollution can be achieved if a prior knowledge of the distribution of rainfall characteristics is known. Rainfall intensity, particularly in tropical climate, plays a major role in the design of runoff conveyance and erosion control systems. This study is aimed to explore the statistical distribution of rainfall intensity for Peninsular Malaysia using hourly rainfall data. Approach: Hourly rainfall data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 11 publications
(11 reference statements)
2
16
0
Order By: Relevance
“…These result is differ from the finding by Mohd Daud et al [14], which stated that GEV is the most suitable distribution for annual maximum rainfall in Peninsular Malaysia. However, it is in agreement with those obtained by Dan'azumi et al [16] where in their study, GP is found to be the most suitable distribution for modelling the hourly rainfall intensity in Peninsular Malaysia. Furthermore, this findings are in accord with another study by Wan Zin et al [17], indicating that GP is the most frequently selected fitting distribution of annual maximum rainfall in Peninsular Malaysia based on LQ-moment methods, together with Generalized Logistic distribution.…”
Section: Goodness Of Fit Test Resultssupporting
confidence: 82%
“…These result is differ from the finding by Mohd Daud et al [14], which stated that GEV is the most suitable distribution for annual maximum rainfall in Peninsular Malaysia. However, it is in agreement with those obtained by Dan'azumi et al [16] where in their study, GP is found to be the most suitable distribution for modelling the hourly rainfall intensity in Peninsular Malaysia. Furthermore, this findings are in accord with another study by Wan Zin et al [17], indicating that GP is the most frequently selected fitting distribution of annual maximum rainfall in Peninsular Malaysia based on LQ-moment methods, together with Generalized Logistic distribution.…”
Section: Goodness Of Fit Test Resultssupporting
confidence: 82%
“…Many Studies discussed some aspects of Water awareness such as- (Damanhouri, 2010;Dan'azumi et al, 2010) that study discuses the effect of raising the environmental awareness on reducing kitchen water, the result showed that the average consumption of kitchen water was 59/L/day/family, reduced after raising environmental awareness to 49.5 L/day/family, with an average of 9.5 L/day/ /family, which is very vital indicator. Anderson (2010) discussed unclean drinking water and concluded that the household don't have alternatives for water treatment; only 19%of them treated drinking water used the following means:-boiling 51.3%,chemical treatment 42.3%, filtering 6.1%, others3%.The study also showed that boiling unclean drinking water needs more amount of water, increased more consumption of foul, requires additional household labor and chemical treatment was more desirable, it's coasted more money in situation where households were very poor.…”
Section: Matrials and Methodsmentioning
confidence: 99%
“…Four candidate distributions, namely, Exponential, Gamma, Weibull and Mixed exponential were tested from twelve stations in Wilayah Persekutuan, Malaysia, and it was concluded that the Mixed exponential distribution fits better for hourly rainfall in the area [9]. Hourly rainfall data was used to study the statistical distribution of rainfall depth and rainfall intensity for Peninsular Malaysia and four candidate distributions namely, Generalized pareto, Exponential, Beta and Gamma were tested and the result indicated that models can be used to fit rainfall depth and intensity for Peninsular Malaysia [10].…”
Section: Introductionmentioning
confidence: 99%